Long term corrosion experiment of steel rebar in fly ash-based geopolymer concrete in nacl solution - Asmara, Y. P.; Siregar, J. P.; Tezara, C.; Wan Nurlisa, Wan Nurlisa; Jamiluddin, J. (Hindawi, 2016)
This research focuses on an experimental investigation to identify the effects of fly ash on the electrochemical process of concrete during the curing time. A rebar was analysed using potentiostat to measure the rest potential, polarization diagram, and corrosion rate. Water-to-cement ratio and amount of fly ash were varied. After being cured for 24 hours at a temperature of 65∘ C, the samples were immersed in 3.5% of NaCl solution for 365 days for electrochemical measurement. Measurements of the half-cell potential and corrosion current density indicated that the fly ash has significant effects on corrosion behaviour of concrete. Although fly ash tends to create passivity on anodic current, it increases corrosion rate. The corrosion potential of this concrete mixture decreases compared to concrete without fly ash. From the result, it can be summarized that concrete mixture with 70% of OPC (Ordinary Portland Cement) and 30% fly ash has shown the best corrosion resistance.